2020
DOI: 10.1016/j.omto.2020.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of MYCN-Amplified Neuroblastoma Cells by Telomerase-Targeted Oncolytic Virus via MYCN Suppression

Abstract: Neuroblastoma (NB) is a primary malignant tumor of the peripheral sympathetic nervous system. High-risk NB is characterized by MYCN amplification and human telomerase reverse transcriptase (hTERT) rearrangement, contributing to hTERT activation and a poor outcome. For targeting hTERT-activated tumors, we developed two oncolytic adenoviruses, OBP-301 and tumor suppressor p53-armed OBP-702, in which the hTERT promoter drives expression of the viral E1 gene for tumor-specific virus replication. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“… 19 , 20 We have further developed OBP-702 as a modification of OBP-301 that expresses the wild-type p53 gene, so OBP-702 can suppress the viability of various types of tumor cells more efficiently compared with OBP-301 via exogenous p53 overexpression in tumor cells. 21 , 22 , 23 The i.p. administration of antitumor agents is advantageous for peritoneal metastasis compared with systemic therapy, because these agents can reach the peritoneal cavity directly in high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 20 We have further developed OBP-702 as a modification of OBP-301 that expresses the wild-type p53 gene, so OBP-702 can suppress the viability of various types of tumor cells more efficiently compared with OBP-301 via exogenous p53 overexpression in tumor cells. 21 , 22 , 23 The i.p. administration of antitumor agents is advantageous for peritoneal metastasis compared with systemic therapy, because these agents can reach the peritoneal cavity directly in high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…EFS-related prognostic risk score values were higher in patients aged ⩾18 versus <18 months ( P = 8.560 × 10 − 13 ); in patients with undifferentiated versus differentiated tumors (P = 2.032 × 10 − 4 ); in the high-risk versus low-risk group (as grouped by the COG risk group) ( P = 1.455 × 10 − 16 ); in the high- and intermediate-risk groups versus the low-risk group (as grouped by MKI) ( P = 1.310 × 10 − 8 ); in patients with stage 4 versus stages 1, 2, and 3 disease ( P = 8.172 × 10 − 12 ); in patients with diploid (DNA index [DI] = 1) versus hyperdiploid (DI > 1) status ( P = .003); in patients with MYCN -amplified versus MYCN -nonamplified status ( P = 3.157 × 10 − 18 ); and in the unfavorable versus favorable group ( P = 7.166 × 10 − 16 ) in the training cohort ( Figure 8A–H ). EFS-related prognostic risk score values were also higher in patients aged ⩾18 versus <18 months ( P = 5.355 × 10 − 10 ); in MYCN -amplified versus MYCN -nonamplified disease ( P = 1.106 × 10 − 16 ); in high-risk versus low-risk patients ( P = 4.33 × 10 − 19 ); and in patients with stage 4 versus stages 1, 2, and 3 disease ( P = 1.693 × 10 − 11 ) in the validation cohort ( Figure 8I–L ). Among the 493 patients with NB in the validation cohort, data on tumor grade, MKI, and histology were lacking; therefore, the relationship between these factors and the prognostic risk score could not be analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the adenoviruses OBP-301 and OBP-702, the tumor specificity of which is driven by the hTERT promoter, have been evaluated. The authors showed that treatment with either of these viruses produced an antitumor response in cell lines with high hTERT expression and reduced growth in a subcutaneous neuroblastoma model ( 51 ). Other approaches have employed cellular carriers to deliver the virus such as Celyvir; autologous MSCs loaded with Icovir-5 (an adenovirus dependent on an aberrant RB pathway).…”
Section: Preclinical Studies Using Virotherapy In Pediatric Solid Tumorsmentioning
confidence: 99%